PENGGUNAAN KATA ALLAH DALAM ALKITAB TERJEMAHAN BARU INDONESIA - Made Nopen Supriadi (Sekolah Tinggi Teologi Arastamar Bengkulu, 2016)
Many people know Jesus Christ and believe he is the Savior, even though that person calls the word God. But many also today claim that the word 'Allah' only has a certain group and is a proper name. This situation created the birth of two groups that were pros and cons in using the word Allah. What is the answer for Christians who keep using the word God? Is it sinful to mention the word Allah? what is the meaning of the word God in the Christian faith? Then how is the history of the word God used? These questions will be answered in the following article. The following article is expected to help believers understand the answers to these problems.